Base material for ultralow-moisture single-component condensed type organic silicon sealant and preparation method of base material
By using acetic anhydride and dimethyl carbonate as dehydration stabilizers in the production of single-component condensation silicone sealant base material and dehydration using a three-stage process, the problem of difficulty in reducing the moisture content of the base material is solved, and the long-term storage and high mechanical properties of the sealant are achieved.
Patent Information
- Application Number
- CN202411988599.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-03-21
AI Technical Summary
The moisture content of the existing one-component condensation silicone sealant base is difficult to reduce to below 400ppm, resulting in poor storage stability and mechanical properties of the sealant.
Acetic anhydride and dimethyl carbonate are used as dehydration stabilizers, and dehydration is carried out through a three-stage process, including introducing a small amount of air flow during the dehydration period to take away the water vapor, and inhaling the dehydration stabilizer with negative pressure in the later stage of dehydration to further remove moisture, ensuring that the moisture content of the base material is controlled below 400ppm.
It effectively reduces the moisture content of the base material, extends the shelf life of the sealant, improves the mechanical properties, and reduces the use of crosslinking agents, reducing production costs.
Smart Images

Figure BDA0005223144740000091 
Figure BDA0005223144740000101 
Figure BDA0005223144740000102
Abstract
Description
Technical Field
[0001] The invention relates to the field of organic silicon materials, and in particular to a base material for ultra-low moisture single-component condensation type organic silicon sealant and a preparation method thereof. Background Art
[0002] One-component condensation type silicone sealant is an important component of silicone materials. This type of silicone sealing material is widely used and has good bonding properties to conventional substrates. When used, this type of material absorbs free water molecules in the air and releases small methanol molecules to undergo cross-linking and curing. Common one-component condensation type silicone sealants are mainly composed of base materials (α, ω-dihydroxy polydimethylsiloxane, nano calcium carbonate, etc.), plasticizers, cross-linking agents, catalysts, and coupling agents. Among them, the composition of the base material is extremely important and determines the key indicators of the sealant, such as mechanical properties, aging resistance, storage stability, etc. The moisture content of the base material directly determines the quality of the storage stability of the sealant. How to reduce the moisture content of the base material has always been a matter of great concern to sealant manufacturers and they have worked hard to do it well.
[0003] The source of moisture in the base material is mainly the moisture contained in nano-calcium carbonate, because nano-calcium carbonate is a kind of reinforcing filler with a high specific surface area formed by nano-scale calcium carbonate particles aggregated together. The moisture on the surface of nano-calcium particles can be removed by heating and vacuuming, but the moisture inside the particles is very difficult to remove in a short time. After the silicone sealant is prepared, the moisture inside will be slowly released over time, and the storage stability of the sealant is seriously affected.
[0004] The general method of base material production is: first mix α, ω-dihydroxy polydimethylsiloxane, nano calcium carbonate and other raw materials in a kneader, and start heating at the same time. When the material temperature rises to above 120℃ and the vacuum degree reaches above -0.085MPa, start dehydration, which lasts for more than 3 hours. The moisture content of the base material can be controlled at 600-900ppm, and then cool down and seal the material for discharging. It is used to produce conventional single-component condensation products, and the storage period can reach more than 12 months at best. Theoretical speculation and experimental proof show that the moisture in the base material will gradually react with the crosslinking agent and catalyst during storage, and the generated alcohol substances will degrade the ω-dihydroxy polydimethylsiloxane polymer under the action of organic amine and organic metal catalyst, which will seriously affect the later curing, especially the mechanical properties will be seriously reduced. If the moisture content can be reduced to below 400ppm, the storage period of silicone sealant can be greatly extended, even up to 24 months, and the amount of crosslinking agent added can also be reduced, which can reduce the cost and improve the mechanical properties.
[0005] The existing methods of reducing the moisture content of the base material by increasing the dehydration temperature, increasing the dehydration vacuum, extending the dehydration time, and adding alkoxysilane dehydrating agents are not ideal and cannot be used in actual production. The base material produced is difficult to meet the demand for products with low moisture content. Summary of the invention
[0006] The main purpose of the present invention is to provide a base material for ultra-low moisture single-component condensation type silicone sealant and a preparation method, which can effectively solve the problems in the background technology.
[0007] To achieve the above object, the technical solution adopted by the present invention is:
[0008] A base material for ultra-low moisture single-component condensation type organic silicon sealant comprises α, ω-dihydroxy polydimethylsiloxane, nano calcium carbonate and a dehydration stabilizer, wherein the weight ratio of the α, ω-dihydroxy polydimethylsiloxane to the nano calcium carbonate is 45:55-55:45; the dehydration stabilizer comprises acetic anhydride and dimethyl carbonate, wherein the weight ratio of the acetic anhydride to the dimethyl carbonate is 1:2, and the amount of the dehydration stabilizer is 1.5%-4% of the total amount of the α, ω-dihydroxy polydimethylsiloxane and the nano calcium carbonate.
[0009] Preferably, the weight ratio of the α,ω-dihydroxy polydimethylsiloxane and the nano-calcium carbonate is 50:50; and the amount of the dehydration stabilizer is 1.5% of the total amount of the α,ω-dihydroxy polydimethylsiloxane and the nano-calcium carbonate.
[0010] Preferably, the weight ratio of the α,ω-dihydroxy polydimethylsiloxane to the nano-calcium carbonate is 50-50; the dehydration stabilizer comprises acetic anhydride and dimethyl carbonate, and the amount of the dehydration stabilizer is 4% of the total amount of the α,ω-dihydroxy polydimethylsiloxane and the nano-calcium carbonate.
[0011] Preferably, the weight ratio of the α,ω-dihydroxy polydimethylsiloxane to the nano-calcium carbonate is 45-55; the dehydration stabilizer comprises acetic anhydride and dimethyl carbonate, and the amount of the dehydration stabilizer is 2.5% of the total amount of the α,ω-dihydroxy polydimethylsiloxane and the nano-calcium carbonate.
[0012] Preferably, the weight ratio of the α,ω-dihydroxy polydimethylsiloxane to the nano-calcium carbonate is 55-45; the dehydration stabilizer comprises acetic anhydride and dimethyl carbonate, and the amount of the dehydration stabilizer is 2.5% of the total amount of the α,ω-dihydroxy polydimethylsiloxane and the nano-calcium carbonate.
[0013] A method for preparing a base material for an ultra-low moisture single-component condensation type silicone sealant comprises the following steps:
[0014] S1: preparing raw materials for preparation, including α, ω-dihydroxy polydimethylsiloxane, nano calcium carbonate, and a dehydration stabilizer;
[0015] S2: prepare the preparation equipment, including a kneading machine with a stirring and heating structure, a pressure relief valve, and a feeding hole;
[0016] S3: adding α, ω-dihydroxy polydimethylsiloxane and nano calcium carbonate into a kneader according to weight percentage, stirring and heating, until the α, ω-dihydroxy polydimethylsiloxane and nano calcium carbonate are evenly mixed;
[0017] S4: After α, ω-dihydroxy polydimethylsiloxane and nano calcium carbonate are uniformly mixed, the temperature in the kneader is raised to 120°C, and the vacuum is turned on until it reaches above -0.095MPa, and then dehydrated for 1 hour;
[0018] S5: Open the pressure relief valve and adjust the vacuum degree in the kneader to maintain it at -0.08MPa, so that a small amount of air flows into the inner cavity of the kneader until the water vapor in the kneader is taken away. Continue for 1 hour, and then use the negative pressure to inhale a specified amount of dehydration stabilizer through the feeding hole. Keep the vacuum degree above -0.095MPa and continue to dehydrate for 1 hour before discharging the material. In this way, the preparation of the base material for ultra-low moisture single-component condensation type silicone sealant is completed, and it can be sealed, cooled and stored.
[0019] Preferably, the preparation method of the dehydration stabilizer is: acetic anhydride and dimethyl carbonate are quickly and evenly mixed in a weight ratio of 1:2, sealed and allowed to stand, and used after storage for 48 hours.
[0020] Compared with the prior art, the present invention has the following beneficial effects:
[0021] Acetic anhydride-dimethyl carbonate is selected as the dehydration stabilizer of the base material, because acetic anhydride and dimethyl carbonate can easily react with water at high temperature and have very good mutual solubility with the base material, which is conducive to spreading on the surface of nano-calcium carbonate particles and diffusing into the nano-calcium carbonate particles, and then reacting with the water inside. The acetic acid produced by the reaction of acetic anhydride with water at high temperature can either react with calcium carbonate to form calcium acetate or be pumped away; the methanol and carbon dioxide produced by the reaction of dimethyl carbonate with water at high temperature can be easily pumped away and will not affect the subsequent production of sealants, and the small amount of residual acetic anhydride and dimethyl carbonate, even if not completely removed, will not affect the various performances of the silicone sealant.
[0022] The conventional base material production process has been optimized, and a three-stage process has been adopted for dehydration. In particular, a small amount of residual water vapor is brought out by introducing a small amount of air flow in the middle stage of dehydration; in the late stage of base material dehydration, a dehydration stabilizer is inhaled by negative pressure, so that the excess dehydration stabilizer reacts with water at high temperature, further removing the water in the nano calcium carbonate particles, and finally controlling the water content of the base material below 400ppm. DETAILED DESCRIPTION
[0023] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0024] A base material for ultra-low moisture single-component condensation type organic silicon sealant comprises α, ω-dihydroxy polydimethylsiloxane, nano calcium carbonate and a dehydration stabilizer, wherein the weight ratio of the α, ω-dihydroxy polydimethylsiloxane to the nano calcium carbonate is 45:55-55:45; the dehydration stabilizer comprises acetic anhydride and dimethyl carbonate, wherein the weight ratio of the acetic anhydride to the dimethyl carbonate is 1:2, and the amount of the dehydration stabilizer is 1.5%-4% of the total amount of the α, ω-dihydroxy polydimethylsiloxane and the nano calcium carbonate.
[0025] A method for preparing a base material for an ultra-low moisture single-component condensation type silicone sealant comprises the following steps:
[0026] S1: preparing raw materials for preparation, including α, ω-dihydroxy polydimethylsiloxane, nano calcium carbonate, and a dehydration stabilizer. The preparation method of the dehydration stabilizer is: quickly and evenly mix acetic anhydride and dimethyl carbonate in a weight ratio of 1:2, seal and let stand, and use after storing for 48 hours;
[0027] S2: prepare the preparation equipment, including a kneading machine with a stirring and heating structure, a pressure relief valve, and a feeding hole;
[0028] S3: adding α, ω-dihydroxy polydimethylsiloxane and nano calcium carbonate into a kneader according to weight percentage, stirring and heating, until the α, ω-dihydroxy polydimethylsiloxane and nano calcium carbonate are evenly mixed;
[0029] S4: After α, ω-dihydroxy polydimethylsiloxane and nano calcium carbonate are uniformly mixed, the temperature in the kneader is raised to 120°C, and the vacuum is turned on until it reaches above -0.095MPa, and then dehydrated for 1 hour;
[0030] S5: Open the pressure relief valve and adjust the vacuum degree in the kneader to maintain it at -0.08MPa, so that a small amount of air flows into the inner cavity of the kneader until the water vapor in the kneader is taken away. Continue for 1 hour, and then use the negative pressure to inhale a specified amount of dehydration stabilizer through the feeding hole. Keep the vacuum degree above -0.095MPa and continue to dehydrate for 1 hour before discharging the material. In this way, the preparation of the base material for ultra-low moisture single-component condensation type silicone sealant is completed, and it can be sealed, cooled and stored. Specific embodiment one:
[0032] A base material for ultra-low moisture single-component condensation type organic silicon sealant comprises α, ω-dihydroxy polydimethylsiloxane, nano-calcium carbonate and a dehydration stabilizer. The dehydration stabilizer comprises acetic anhydride and dimethyl carbonate. The weight ratio of acetic anhydride to dimethyl carbonate is 1:2. The weight ratio of α, ω-dihydroxy polydimethylsiloxane to nano-calcium carbonate is 50:50. The amount of the dehydration stabilizer is 1.5% of the total amount of the α, ω-dihydroxy polydimethylsiloxane and the nano-calcium carbonate.
[0033] A method for preparing a base material for an ultra-low moisture single-component condensation type silicone sealant comprises the following steps:
[0034] S1: preparing raw materials for preparation, including α, ω-dihydroxy polydimethylsiloxane, nano calcium carbonate, and a dehydration stabilizer. The preparation method of the dehydration stabilizer is: quickly and evenly mix acetic anhydride and dimethyl carbonate in a weight ratio of 1:2, seal and let stand, and use after storing for 48 hours;
[0035] S2: prepare the preparation equipment, including a kneading machine with a stirring and heating structure, a pressure relief valve, and a feeding hole;
[0036] S3: adding α, ω-dihydroxy polydimethylsiloxane and nano calcium carbonate into a kneader according to weight percentage, stirring and heating, until the α, ω-dihydroxy polydimethylsiloxane and nano calcium carbonate are evenly mixed;
[0037] S4: After α, ω-dihydroxy polydimethylsiloxane and nano calcium carbonate are uniformly mixed, the temperature in the kneader is raised to 120°C, and the vacuum is turned on until it reaches above -0.095MPa, and then dehydrated for 1 hour;
[0038] S5: Open the pressure relief valve and adjust the vacuum degree in the kneader to maintain it at -0.08MPa, so that a small amount of air flows into the inner cavity of the kneader until the water vapor in the kneader is taken away. Continue for 1 hour, and then use the negative pressure to inhale a specified amount of dehydration stabilizer through the feeding hole. Keep the vacuum degree above -0.095MPa and continue to dehydrate for 1 hour before discharging the material. In this way, the preparation of the base material for ultra-low moisture single-component condensation type silicone sealant is completed, and it can be sealed, cooled and stored. Specific embodiment 2:
[0040] A base material for ultra-low moisture single-component condensation type organic silicon sealant comprises α, ω-dihydroxy polydimethylsiloxane, nano calcium carbonate and a dehydration stabilizer. The dehydration stabilizer comprises acetic anhydride and dimethyl carbonate. The weight ratio of acetic anhydride to dimethyl carbonate is 1:2. The weight ratio of α, ω-dihydroxy polydimethylsiloxane to nano calcium carbonate is 50-50. The amount of the dehydration stabilizer is 4% of the total amount of the α, ω-dihydroxy polydimethylsiloxane and the nano calcium carbonate.
[0041] A method for preparing a base material for an ultra-low moisture single-component condensation type silicone sealant comprises the following steps:
[0042] S1: preparing raw materials for preparation, including α, ω-dihydroxy polydimethylsiloxane, nano calcium carbonate, and a dehydration stabilizer. The preparation method of the dehydration stabilizer is: quickly and evenly mix acetic anhydride and dimethyl carbonate in a weight ratio of 1:2, seal and let stand, and use after storing for 48 hours;
[0043] S2: prepare the preparation equipment, including a kneading machine with a stirring and heating structure, a pressure relief valve, and a feeding hole;
[0044] S3: adding α, ω-dihydroxy polydimethylsiloxane and nano calcium carbonate into a kneader according to weight percentage, stirring and heating, until the α, ω-dihydroxy polydimethylsiloxane and nano calcium carbonate are evenly mixed;
[0045] S4: After α, ω-dihydroxy polydimethylsiloxane and nano calcium carbonate are uniformly mixed, the temperature in the kneader is raised to 120°C, and the vacuum is turned on until it reaches above -0.095MPa, and then dehydrated for 1 hour;
[0046] S5: Open the pressure relief valve and adjust the vacuum degree in the kneader to maintain it at -0.08MPa, so that a small amount of air flows into the inner cavity of the kneader until the water vapor in the kneader is taken away. Continue for 1 hour, and then use the negative pressure to inhale a specified amount of dehydration stabilizer through the feeding hole. Keep the vacuum degree above -0.095MPa and continue to dehydrate for 1 hour before discharging the material. In this way, the preparation of the base material for ultra-low moisture single-component condensation type silicone sealant is completed, and it can be sealed, cooled and stored. Specific embodiment three:
[0048] A base material for ultra-low moisture single-component condensation type organic silicon sealant comprises α, ω-dihydroxy polydimethylsiloxane, nano-calcium carbonate and a dehydration stabilizer. The dehydration stabilizer comprises acetic anhydride and dimethyl carbonate. The weight ratio of acetic anhydride to dimethyl carbonate is 1:2. The weight ratio of α, ω-dihydroxy polydimethylsiloxane to nano-calcium carbonate is 45-55. The amount of the dehydration stabilizer is 2.5% of the total amount of the α, ω-dihydroxy polydimethylsiloxane and the nano-calcium carbonate.
[0049] A method for preparing a base material for an ultra-low moisture single-component condensation type silicone sealant comprises the following steps:
[0050] S1: preparing raw materials for preparation, including α, ω-dihydroxy polydimethylsiloxane, nano calcium carbonate, and a dehydration stabilizer. The preparation method of the dehydration stabilizer is: quickly and evenly mix acetic anhydride and dimethyl carbonate in a weight ratio of 1:2, seal and let stand, and use after storing for 48 hours;
[0051] S2: prepare the preparation equipment, including a kneading machine with a stirring and heating structure, a pressure relief valve, and a feeding hole;
[0052] S3: adding α, ω-dihydroxy polydimethylsiloxane and nano calcium carbonate into a kneader according to weight percentage, stirring and heating, until the α, ω-dihydroxy polydimethylsiloxane and nano calcium carbonate are evenly mixed;
[0053] S4: After α, ω-dihydroxy polydimethylsiloxane and nano calcium carbonate are uniformly mixed, the temperature in the kneader is raised to 120°C, and the vacuum is turned on until it reaches above -0.095MPa, and then dehydrated for 1 hour;
[0054] S5: Open the pressure relief valve and adjust the vacuum degree in the kneader to maintain it at -0.08MPa, so that a small amount of air flows into the inner cavity of the kneader until the water vapor in the kneader is taken away. Continue for 1 hour, and then use the negative pressure to inhale a specified amount of dehydration stabilizer through the feeding hole. Keep the vacuum degree above -0.095MPa and continue to dehydrate for 1 hour before discharging the material. In this way, the preparation of the base material for ultra-low moisture single-component condensation type silicone sealant is completed, and it can be sealed, cooled and stored. Specific embodiment four:
[0056] The invention discloses a base material for ultra-low moisture single-component condensation type organic silicon sealant, comprising α, ω-dihydroxy polydimethylsiloxane, nano-calcium carbonate and a dehydration stabilizer. The dehydration stabilizer comprises acetic anhydride and dimethyl carbonate, wherein the weight ratio of acetic anhydride to dimethyl carbonate is 1:2, and the weight ratio of α, ω-dihydroxy polydimethylsiloxane to nano-calcium carbonate is 55-45. The amount of the dehydration stabilizer is 2.5% of the total amount of the α, ω-dihydroxy polydimethylsiloxane and the nano-calcium carbonate.
[0057] A method for preparing a base material for an ultra-low moisture single-component condensation type silicone sealant comprises the following steps:
[0058] S1: preparing raw materials for preparation, including α, ω-dihydroxy polydimethylsiloxane, nano calcium carbonate, and a dehydration stabilizer. The preparation method of the dehydration stabilizer is: quickly and evenly mix acetic anhydride and dimethyl carbonate in a weight ratio of 1:2, seal and let stand, and use after storing for 48 hours;
[0059] S2: prepare the preparation equipment, including a kneading machine with a stirring and heating structure, a pressure relief valve, and a feeding hole;
[0060] S3: adding α, ω-dihydroxy polydimethylsiloxane and nano calcium carbonate into a kneader according to weight percentage, stirring and heating, until the α, ω-dihydroxy polydimethylsiloxane and nano calcium carbonate are evenly mixed;
[0061] S4: After α, ω-dihydroxy polydimethylsiloxane and nano calcium carbonate are uniformly mixed, the temperature in the kneader is raised to 120°C, and the vacuum is turned on until it reaches above -0.095MPa, and then dehydrated for 1 hour;
[0062] S5: Open the pressure relief valve and adjust the vacuum degree in the kneader to maintain it at -0.08MPa, so that a small amount of air flows into the inner cavity of the kneader until the water vapor in the kneader is taken away. Continue for 1 hour, and then use the negative pressure to inhale a specified amount of dehydration stabilizer through the feeding hole. Keep the vacuum degree above -0.095MPa and continue to dehydrate for 1 hour before discharging the material. In this way, the preparation of the base material for ultra-low moisture single-component condensation type silicone sealant is completed, and it can be sealed, cooled and stored.
[0063] The existing methods for reducing the moisture content of the base material are summarized in the following table:
[0064]
[0065]
[0066] It can be seen from this that the current methods are not ideal and cannot be used in actual production, and the base materials produced are difficult to meet the demand for products with low moisture content. Specific embodiment five:
[0068] Based on the preparation of the base material of specific examples 1-4 and the prior art, the specific examples 1-4 are recorded as examples 1-4, and the prior art is recorded as comparative examples 1-3. The following is a composition table:
[0069]
[0070] The preparation method of the comparative base material is as follows: α, ω-dihydroxypolydimethylsiloxane and nano calcium carbonate are added into a kneader in the composition proportions, stirring and heating are started, after the materials are evenly mixed, the material temperature rises to 120°C, vacuum is turned on, and the temperature reaches above -0.095MPa, and timing is started. After 3 hours, the material can be discharged, sealed, cooled and stored.
[0071] Preparation of demethanol type silicone sealant based on Examples 1-4 and Comparative Examples 1-3:
[0072] The invention comprises base material (example / comparative example): 1000; methyltrimethoxysilane: 30; titanate catalyst: 14; and KH560 coupling agent: 3.5.
[0073] Methyltrimethoxysilane was added to the base materials of the examples and comparative examples respectively, and the mixture was evenly dispersed by vacuum stirring. Then, the titanate catalyst and the coupling agent were evenly mixed and added to the above materials together, and the mixture was evenly dispersed by vacuum stirring. The discharged materials were sealed and stored, and the test products of Examples 1, 2, 3, 4, and Comparative Examples 1, 2, 3 were obtained respectively.
[0074] Performance Test:
[0075] Base material moisture content test: Use C20 Coulometric Karl Fischer moisture analyzer (with D0308 drying oven) for testing, sample temperature is 250℃, the results are as follows:
[0076]
[0077] From the moisture content test results, it can be seen that the moisture content of the embodiments is 298-387 ppm, all below 400 ppm; while the moisture content of the comparative example is 637-752 ppm. It can be seen that the moisture content of the embodiments is much lower than that of the comparative example, so it can be seen that the low moisture content solution provided by the present invention is very effective.
[0078] Organic silicon sealant performance test: surface drying time test reference: GB / T13477.5-2017 building sealing material test method; Shore A hardness test reference: GB / T531.1-2008 vulcanized rubber or thermoplastic rubber indentation hardness test method; tensile performance test (maximum strength, maximum strength elongation, bonding failure area) reference: GB16776-2005 building silicone structural sealant; storage period test: indoor conditions, temperature 25±2℃, humidity 55±5%, surface drying time and 24-hour strip curing condition are tested every 30 days. At the same time, if the surface drying time is ≤60min and the 24-hour strip curing is normal, it is judged to be within the storage period. The following is the test table:
[0079]
[0080]
[0081] From the comparative performance test, it can be seen that the embodiment and the comparative example are almost the same in terms of surface drying time, hardness, maximum bonding strength, maximum strength elongation, bonding failure area, etc., reaching or exceeding the corresponding national standards, and the storage period of the embodiment is much longer than that of the comparative example. It can be seen that the base material prepared by the scheme provided by the present invention is used for the production of silicone sealant, and the obtained product has qualified performance, which is equivalent to the silicone sealant produced by preparing the base material by the conventional scheme, but the former has a huge advantage in storage period, which is not comparable to conventional products.
[0082] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A base material for ultra-low moisture single-component condensation type silicone sealant, comprising α, ω-dihydroxy polydimethylsiloxane, nano calcium carbonate, and a dehydration stabilizer, characterized in that: The weight ratio of the α,ω-dihydroxy polydimethylsiloxane and the nano-calcium carbonate is 45:55-55:45; the dehydration stabilizer comprises acetic anhydride and dimethyl carbonate, the weight ratio of the acetic anhydride and dimethyl carbonate is 1:2, and the amount of the dehydration stabilizer is 1.5%-4% of the total amount of the α,ω-dihydroxy polydimethylsiloxane and the nano-calcium carbonate.
2. The ultra-low moisture one-component condensation type silicone sealant base material according to claim 1, characterized in that: The weight ratio of the α,ω-dihydroxy polydimethylsiloxane and the nano calcium carbonate is 50:50; the amount of the dehydration stabilizer is 1.5% of the total amount of the α,ω-dihydroxy polydimethylsiloxane and the nano calcium carbonate.
3. The ultra-low moisture one-component condensation type silicone sealant base material according to claim 1, characterized in that: The weight ratio of the α,ω-dihydroxy polydimethylsiloxane and the nano calcium carbonate is 50-50; the dehydration stabilizer comprises acetic anhydride and dimethyl carbonate, and the amount of the dehydration stabilizer is 4% of the total amount of the α,ω-dihydroxy polydimethylsiloxane and the nano calcium carbonate.
4. The ultra-low moisture one-component condensation type silicone sealant base material according to claim 1, characterized in that: The weight ratio of the α,ω-dihydroxy polydimethylsiloxane to the nano calcium carbonate is 45-55; the dehydration stabilizer comprises acetic anhydride and dimethyl carbonate, and the amount of the dehydration stabilizer is 2.5% of the total amount of the α,ω-dihydroxy polydimethylsiloxane and the nano calcium carbonate.
5. The ultra-low moisture one-component condensation type silicone sealant base material according to claim 1, characterized in that: The weight ratio of the α,ω-dihydroxy polydimethylsiloxane to the nano calcium carbonate is 55-45; the dehydration stabilizer comprises acetic anhydride and dimethyl carbonate, and the amount of the dehydration stabilizer is 2.5% of the total amount of the α,ω-dihydroxy polydimethylsiloxane and the nano calcium carbonate.
6. A method for preparing a base material for ultra-low moisture one-component condensation type silicone sealant, using the base material for ultra-low moisture one-component condensation type silicone sealant according to any one of claims 1 to 5, characterized in that: The steps include: S1: preparing raw materials for preparation, including α, ω-dihydroxy polydimethylsiloxane, nano calcium carbonate, and a dehydration stabilizer; S2: prepare the preparation equipment, including a kneading machine with a stirring and heating structure, a pressure relief valve, and a feeding hole; S3: adding α, ω-dihydroxy polydimethylsiloxane and nano calcium carbonate into a kneader according to weight percentage, stirring and heating, until the α, ω-dihydroxy polydimethylsiloxane and nano calcium carbonate are evenly mixed; S4: After α, ω-dihydroxy polydimethylsiloxane and nano calcium carbonate are uniformly mixed, the temperature in the kneader is raised to 120°C, and the vacuum is turned on until it reaches above -0.095MPa, and then dehydrated for 1 hour; S5: Open the pressure relief valve and adjust the vacuum degree in the kneader to maintain it at -0.08MPa, so that a small amount of air flows into the inner cavity of the kneader until the water vapor in the kneader is taken away. Continue for 1 hour, and then use the negative pressure to inhale a specified amount of dehydration stabilizer through the feeding hole. Keep the vacuum degree above -0.095MPa and continue to dehydrate for 1 hour before discharging the material. In this way, the preparation of the base material for ultra-low moisture single-component condensation type silicone sealant is completed, and it can be sealed, cooled and stored.
7. The method for preparing a base material for ultra-low moisture one-component condensation type silicone sealant according to claim 6, characterized in that: The preparation method of the dehydration stabilizer is: acetic anhydride and dimethyl carbonate are mixed quickly and uniformly in a weight ratio of 1:2, sealed and allowed to stand, and used after being stored for 48 hours.